2020
DOI: 10.17816/mechnikov202012227-38
|View full text |Cite
|
Sign up to set email alerts
|

Current, effectiveness of therapy and outcomes of new coronavirus infection: preliminary analysis

Abstract: Relevance. Verification of a new coronavirus infection (COVID-19) requires clear algorithms for the diagnosis and treatment of patients, depending on clinical, laboratory and instrumental dates. Timely and informed decisions on optimizing management tactics and prescribing proactive anti-inflammatory therapy before development of a complete symptom complex life threatening conditions are needed in some cases. Aim of the study. To analyze the course and outcomes of a new coronavirus infection, depending o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…An innovative approach in the use of monoclonal antibody (mAB) drugs is needed, as up to date an exact and most effective treatment for COVID-19 patients has not yet been developed. It has been shown that a systemic hyperinflammation is often observed with the development of "cytokine storm" and the formation of acute respiratory distress syndrome (ARDS) in COVID-19 patients [1]. However, the exact pathophysiological mechanisms and treatment, especially of severe COVID- 19, have not yet been determined.…”
Section: Introductionmentioning
confidence: 99%
“…An innovative approach in the use of monoclonal antibody (mAB) drugs is needed, as up to date an exact and most effective treatment for COVID-19 patients has not yet been developed. It has been shown that a systemic hyperinflammation is often observed with the development of "cytokine storm" and the formation of acute respiratory distress syndrome (ARDS) in COVID-19 patients [1]. However, the exact pathophysiological mechanisms and treatment, especially of severe COVID- 19, have not yet been determined.…”
Section: Introductionmentioning
confidence: 99%